ACTIVITIES OF INTER-UNIVERSITY RESEARCH INSTITUTE IN THE AREA OF CHEMISTRY AND MATERIALS SCIENCE - Evgeniy L. Mukhanov (Высшее образование в России, 2016)
The paper focuses on the experience of Southern federal university (SFedU) in organization of a inter-university research institute - a division organized for special purpose of complexresearches in the areaof chemistry. The author pointes out that within the structure of SFedU there is organized a Research Institute of physical and organic chemistry with highly qualified research staff. The paper discusses the organization structure of the research institute and the general benefits of such organization connected with reserve of potential employees, integration of modern scientific results and education etc. Main areas of scientific activities of the institute are characterized and a high level of the obtained scientific results is stressed out.